RANCANG BANGUN SISTEM BUDIDAYA TAOGE CERDAS BERBASIS LORA DAN IOT - Fadhli, Mohammad; Cahya Iman, Tri Rizki; Rose, Martinus Mujur (JURNAL TELISKA, 2024)
Cultivating bean sprouts requires regular care for the beans. The required care includes regular watering and maintaining temperature conditions between 23°C to 28°C with a humidity level of 85% to 90%. In this research, an intelligent sprout cultivation system based on LoRa and IoT has been proposed. This system uses a DHT22 sensor to read the temperature and humidity of the air around the bean sprouts. It sends the data to the gateway using LoRa. The gateway forwards the temperature and humidity data to the Thingspeak server using the MQTT protocol. LoRa allows temperature and humidity monitoring to be carried out via the LoRa local network without an internet connection. The proposed system can also water the bean sprouts automatically if the humidity is < 80% or the last watering time has been ≥ 3 hours. Based on the tests carried out, it can be concluded that the proposed system can work well. During the tests, the DHT22 sensor could respond to changes in temperature and humidity. Sending sensor data to the Thingspeak server could work well. Meanwhile, sensor nodes and gateways could communicate up to a distance of 600 meters using LoRa.